Evaluation of sieved biomass ofÂ Cicer arientinumÂ (horse bean) for removal ofmethylene blue: batch study - Anandrao A Kale (International Journal of Recycling of Organic Waste in Agriculture)
Adsorption of methylene blue by the sieved biomass of Cicer arientinum is conducted in batch mode. The effect of different parameters such as contact time, sorbent dose, pH, and temperature has been studied. The adsorption rises substantially as pH is increased from 2 to 4, and then with the increase to pH 10, there is slight decrease in the percentage of adsorption. This may be due to the electrostatic forces of attraction between [MB]+ cations and the OHâ ions which are greater at low pH in the solution. In the highly acidic medium, there are an ample number of H+ ions. These can neutralize the negative sites on biosorbent surfaces, leading to a lesser adsorption. The Langmuir model fit and Hall separation values indicate favorable adsorption. Thermodynamic parameters via KD and ÎG have also been calculated: the ÎG value at 15°C is â943 J/mole, while at 45°C, the value of ÎG is â4,010 J/mole. At the higher concentration, KD values decrease and the ÎG values become positive in the same temperature range, indicating the spontaneity of the process. Kinetics of biosorption results shows that the sorption process is well explained by a pseudo-second-order model with determination coefficients of 0.4841 to 0.9962 for S-II under all experimental conditions. The sorption mechanism was determined by the Weber and Morris intraparticle diffusion model. For the initial concentration of 79.9 mg/L and material dose of 500 mg/L, the value of Kid and the intercept was found to be 4.359 and 22.557, respectively, indicating that the foundry layer is sufficiently thick. The low-cost, easily available agro-waste of C. arientinum was found to be a good adsorbent for the methylene blue dye.